Variability of jump biomechanics between horses of different age and experience using commercial inertial measurement unit technology - Becker, K.; Lewczuk, D. (Journal of Equine Veterinary Science, 2022)
The application of commercial inertial measurement units has become popular in equestrian sports, which may help to eliminate a gap of knowledge concerning many aspects of biomechanics in training. This study employed the Seaver IMU system to measure jumping characteristics of horses with differing age-competition experience during regular training. It was hypothesized that experience level results in lower variability of jumping parameters. Twelve Warmblood horses aged 5 to 6 years with/without competition experience and 7 to 11 years with experience were investigated during regular training in 2 training centers. Consistent number of 10 successive jumps of the individual chosen course of vertical and spread obstacles (5th -15th) were analyzed and the following parameters were measured: jump height, reserve and length; taking off angle, acceleration, velocity; jump spatial shifting, energy by landing, and frequency of approach strides. Preliminary analysis confirmed comparable physiological effort in 2 training center based on heart rate, distance and duration measurements. The multifactorial analysis of variance for biomechanical data included in the statistical model the random effect of horse and fixed effects of training center, age-experience group, successive jump number, obstacle type and height. Four parameters were significantly different between the younger, inexperienced group and experienced younger and older horses: height of jump (P = .01), frequency of approach strides (P = .005), acceleration of taking off (P = .01), and energy by landing (P = .0013). Standard errors for almost all the parameters reached higher values for the youngest, inexperienced horses. Variability of jumping parameters was lower for experienced groups of horses, suggesting higher precision on obstacle courses.